The post-socialist city : continuity and change in urban space and imagery - Kliems, Alfrun 1969- Hrsg; Dmitrieva, Marina 1953- Hrsg; Bromby, Louise; Dietz, Christian (Jovis diskurs, 2010)
It is impossible to view urban planning in Socialism apart from its ideological content. Socialist ideas were realised in buildings, the layout of streets and squares, in films, in literature, and fine art. This heritage - even after the collapse of the political system - has survived into the post-socialist city to date. At the end of the last century, however, representative socialist buildings lost their political significance or disappeared from the urban picture altogether. Other buildings from this period were given alternative functions in the course of new urban usage concepts